Self medication practices of over the counter analgesic drugs among medical students in a tertiary care hospital in Jharkhand, India - Kumari, Kusum; Toppo, Mary Sunita; ., Priyanki (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Self-medication is a very common practice which is gradually spreading all over the world. Analgesics are the most commonly available over the counter (OTC) drugs. They are used for pain relief in many diseases. Use of these analgesics has become a serious ailment because self- medication practices of analgesic drugs are increasing among general population as well as medical students. Being future medical practitioners, self-medication has a special impact in medical students. Various data are available regarding usage of OTC analgesic drugs but still data in Jharkhand are lacking. So, the present study aims to provide an insight into the practice of OTC analgesics among 3rd and 4th year medical students in RIMS, Ranchi, Jharkhand. Methods: It was a cross-sectional study conducted among medical students in RIMS, Ranchi, Jharkhand in November-December 2018. Data were collected through questionnaire filled by the students and results were expressed as percentage frequency. Results: Questionnaire were filled completely by 253 students out of 287 students. 85.8% of males and 90.41% of females were practicing self-medication. Advice from seniors and books were the major source of information about the drugs. Paracetamol was the most common drug used (54.87%) and headache (27.43%) was the most common indication. Mild nature of illness (30.34%) and quick relief (29.10%) were the most common reason of self-medication. About 83.39% of them were using these drugs according to need.50.98% had not felt any side effects. 51.38% students were of the view that self-medication practices are not always acceptable. Conclusions: Medical students use OTC analgesics for various kinds of pain like headache, muscle pain, menstrual pain etc. They generally use different non-steroidal anti-inflammatory drugs (NSAIDS) among which paracetamol is the most common. But self-medication practices are always associated with some risks. So, the students must be educated properly regarding their rational use and advantages and disadvantages of OTC drugs.